Stress, anxiety and depression in Portuguese nursing students - Firmino, Cristiana Furtado (2019)
BACKGROUND: The demands of the Nursing degree and the experience of undergraduate nursing students lead to the occurrence of stress, anxiety and depression AIM: To determine the prevalence of stress, anxiety and depression amongst Portuguese undergraduate nursing students. METHODS: A cross-sectional and descriptive study. Two hundred and fifty-three nursing students from two private schools and two public schools participated in this study. The data collection instrument consisted of sociodemographic and health behavior variables as well as, the Depression Anxiety and Stress Scale (DASS-21)-Short Form. The cut-off scores have been developed for defining mild/moderate/severe/extremely severe scores for each DASS-21 scale. The sociodemographic variables were analyzed using Pearson chi-square analysis for dichotomous data. This study was approved by the Ethics Committee of the two Nursing schools. RESULTS: The prevalence of depression is 43.2%, anxiety 54.2% and stress 45.1%. Depression was classified as mild in 12.3% of the sample, moderate in 13.8%, severe in 7.5% and extremely severe in 9.5%. Anxiety was mild in 18.2%, moderate in 12.3%, severe in 9.5% and extremely severe in 14.2%. Stress was classified as mild in 14.2%, moderate in 11.5%, severe in 13% and extremely severe in 6.3%. A Pearson Chi-Square's analysis revealed a significant relationship between depression and working students; anxiety showed significant relationships with the type of education, working students, marital status and age; stress revealed a significant relation between working students and marital status. CONCLUSIONS: Depression, anxiety and stress are highly prevalent in Portuguese nursing students. It is suggested the use of some interventions that can improve the mental health of nursing students.RESUMO CONTEXTO: As exigências do curso de enfermagem e a experiência de estudantes de enfermagem levam à ocorrência de stresse, ansiedade e depressão. OBJETIVO(S): Determinar a prevalência de stresse, ansiedade e depressão entre estudantes de licenciatura em enfermagem. MÉTODOS: Estudo transversal e descritivo. Duzentos e cinquenta e três estudantes de enfermagem de duas escolas privadas e duas públicas participaram neste estudo. O instrumento de colheita de dados consistiu em variáveis sociodemográficas e comportamentais de saúde e a Escala de Ansiedade, Stresse e Depressão (DASS-21) - Short-Form (Pais-Ribeiro, Honrado, & Leal, 2004). Os scores de corte foram desenvolvidos para definir os scores leve / moderado / severo / extremamente grave para cada escala DASS-21. As variáveis sociodemográficas foram analisadas pela análise qui-quadrado de Pearson para dados dicotómicos. Este estudo foi aprovado pela Comissão de Ética de duas escolas de enfermagem. RESULTADOS: A prevalência de depressão é de 43,1%, ansiedade de 54,2% e stresse de 45,1%. A depressão foi classificada como leve em 12,3% da amostra, moderada em 13,8%, severa em 7,5% e extremamente severa em 9,5%. A ansiedade foi leve em 18,2%, moderada em 12,3%, severa em 9,5% e extremamente severa em 14,2%. O stresse foi classificado como leve em 14,2%, moderado em 11,5%, severo em 13% e extremamente severo em 6,3%. A análise pelo qui-quadrado de Pearson revelou uma associação estatisticamente significativa entre a variável depressão e trabalhador estudante; a ansiedade mostrou associações significativas com o tipo de escolaridade, estudante, estado civil e idade; o stresse revelou associações significativas com as variáveis trabalhadores estudantes e estado civil. CONCLUSÕES: Depressão, ansiedade e stresse são muito prevalentes nos estudantes de enfermagem portugueses. De acordo com nossos resultados, sugere-se a realização de intervenções de apoio aos estudantes de enfermagem que promovam uma melhor saúde mental.